Family Social Support Can Reduce Work Stress In Farmers - Harishoh, Liana Wafdatul; Modest, Bunga Misselvy Lovely; Liandini, Sheila Anugrah; Kurniyawan, Enggal Hadi; Nur, Kholid Rosyidi Muhammad; Afandi, Alfid Tri; Kurniawan, Dicky Endrian (Health Access Journal, 2024)
Farmers often work alone in remote environments with little time to rest or socialize, leading to mental health problems and poor psychological well-being. The imbalance between physical and psychological aspects causes physical responses such as difficulty concentrating, and psychological responses such as anxiety. Social support, self-efficacy, and coping mechanisms play a role in overcoming work-related stress in farmers. This study aims to analyze how family social support can reduce work stress in farmers. The method used in this study is a literature study with 10 articles in 3 databases, namely Google Scholar, Science Direct, and PubMed with a publication period of 2019-2024. Research shows that work stress in farmers can be caused by various factors, namely heavy workloads, long working hours, as well as weather pressure, pests, and changes in market prices. However, it was found that high family social support can reduce work-related stress in farmers but not on farmers' psychological well-being. Therefore, it is necessary to follow up on how family social support affects farmers' work stress and how effective coping strategies can reduce this stress.